The Relationship between Dental Health Knowledge and Adolescent Caries Status at SMA Negeri 9 Banda Aceh - Suryani, Linda; Nurul Syifa, Putroe; Zahara, Elfi (Journal Dental Health, 2023)
The biggest dental and oral health problem commonly encountered is caries. Caries is a universal disease that can occur in all ages, races, socio-economic and genders. One of the important factors causing caries is the lack of maintaining dental and oral hygiene. The value of dental and oral hygiene is important for each individual to know, it plays a role in efforts to prevent the occurrence of caries. The purpose of this study was to determine the Relationship between Dental Health Knowledge and Adolescent Caries Status at SMA Negeri 9 Banda Aceh. This research is analytical with a cross-sectional approach, conducted at SMA Negeri 9 Banda Aceh. The results of the study on adolescent knowledge about dental health are still in the sufficient category, with the status of dental caries in the medium category in adolescents at SMA Negeri 9 Banda Aceh, the most dental health knowledge in the sufficient category as many as 29 people (53.7%), and the status of adolescent caries the most in the moderate category as many as 23 people (42.6%). The results of statistical analysis with the Chi Square test, obtained the significance value of the relationship between dental health knowledge and caries status in adolescents with a P Value value: 0.05. Therefore, adolescents must be more active in seeking information about dental health, in order to avoid the status of caries which greatly affects dental health.